Visceral Artery Aneurysms: Decision Making and Treatment Options in the New Era of Minimally Invasive and Endovascular Surgery - Hosn, Maen Aboul; Xu, Jun; Sharafuddin, Mel; Corson, John D. (International Journal of Angiology, 2019)
The abdominal viscera blood supply is derived from anterior branches of the abdominal aorta. Visceral artery aneurysms (VAAs) include aneurysms of the following arteries and their branches: the celiac artery, the hepatic artery, the splenic artery, the superior mesenteric artery, the inferior mesenteric artery, the pancreaticoduodenal artery, and the gastroduodenal artery. Overall VAAs comprise < 2% of all types of arterial aneurysms. Asymptomatic VAAs are now being encountered more frequently due to the widespread use of advanced diagnostic abdominal imaging. The incidental finding of a VAA frequently leaves clinicians with a dilemma as to the best course of management. The focus of this review is on current treatment options and management guidelines for both symptomatic and asymptomatic VAAs.
Keywords: abdominal viscera blood supply; visceral artery aneurysms and pseudoaneurysms; aneurysm rupture; minimally invasive surgery; endovascular surgery